Trends in leisure time and work-related physical activity in the Spanish working population, 1987-2006 Tendencias en la práctica de actividad física en el tiempo libre y el trabajo en la población española trabajadora, 1987-2006 - Cristina Alonso-Blanco; Domingo Palacios-Ceña; Valentín Hernández-Barrera; Pilar Carrasco-Garrido; Rodrigo Jiménez-García; César Fernández- (Elsevier, 2012)
Objective: To analyze time trends in the prevalence of leisure time (LTPA) and work-related (WRPA) physical activity between 1987 and 2006 in the Spanish working population. Methods: We analyzed data taken from the Spanish National Health Surveys for 1987 (n = 29,647), 1993 (n = 20,707), 1995-1997 (n = 12,800), 2001 (n = 21,058), 2003 (n = 21,650), and 2006 (n = 29,478). The main variables were LTPA and WRPA in working adults aged 18-64 years old. We analyzed sociodemographic characteristics, self-perceived health status, lifestyle habits and associated comorbidities using multivariate logistic regression models. Results: The prevalences of LTPA and WRPA were lower in women than in men (p < 0.05). The practice of LTPA (OR: 1.54, 95%CI: 1.32-1.80 for women; OR = 1.15, 95%CI: 1.02-1.31 for men) and WRPA (OR = 1.73, 95%CI: 1.38-2.19 for women; OR = 1.55, 95%CI: 1.44-1.91 for men) significantly increased from 1987 to 2006. In both genders, the variables associated with a higher likelihood of practicing LTPA were greater age, higher educational level and being an ex- or non-smoker, while negative predictors included being married, worse self-perceived health, and obesity. Factors that increased the probability of reporting WRPA were being married, worse self-rated health status, and sleeping > 8h per day. The only factor that reduced the probability of reporting WRPA was being an ex- or non-smoker. Conclusions: We found an increase in LTPA and WRPA in the last 20 years in the Spanish working population. Several factors were associated with a higher or lower likelihood of practicing LTPA or WRPA in this population. Objetivo: Analizar la tendencia en la práctica de actividad física en el tiempo libre (AFTL) y de actividad física en el tiempo de trabajo (AFTT) entre 1987 y 2006 en la población trabajadora española. Métodos: Se analizaron datos procedentes de la Encuesta Nacional de Salud realizada por el Instituto Nacional de Estadística en 1987 (n = 29.647), 1993 (n = 20.707), 1995-1997 (n = 12.800), 2001 (n = 21.058), 2003 (n = 21.650) y 2006 (n = 29.478). Se analizaron la AFTL y la AFTT en la población trabajadora de 18 a 64 años de edad como variables principales. Se investigaron características sociodemográficas, percepción del estado de salud, hábitos de vida y enfermedades asociadas mediante análisis multivariados. Resultados: Las mujeres mostraron una menor prevalencia de AFTL y AFTT en comparación con los hombres (p <0,05). La práctica de AFTL (odds ratio [OR] = 1,54, intervalo de confianza del 95% [IC95%]: 1,32-1,80 para las mujeres; OR = 1,15, IC95%: 1,02-1,31 para los hombres) y de AFTT (OR = 1,73; IC95%: 1,38-2,19 mujeres; OR = 1,55, IC95%: 1,44-1,91 hombres) aumentó significativamente entre 1987 y 2006. Edad más adulta, nivel educacional más alto y ser ex fumador se asociaron con una mayor práctica de AFTL tanto en hombres como en mujeres, mientras que estar casado, percepción negativa de salud y obesidad se asociaron con una menor práctica de AFTL. Estar casado, percepción negativa de salud y dormir > 8h al día se asociaron a mayor práctica de AFTT, mientras que ser ex fumador se asoció a menor práctica de AFTT. Conclusiones: La práctica de AFTL y AFTT ha aumentado significativamente en los últimos 20 años en la población trabajadora española. Diferentes factores se asocian a una mayor o menor práctica de AFTL y AFTT en esta población.